Factors Associated with the Utilization of the National Health Insurance Mobile Information System - Virta Filantropi Zebua; Rahmad Gurusinga; Barita Aritonang (JURNAL KESMAS DAN GIZI (JKG), 2026)
Mobile JKN is a digital application developed by BPJS Kesehatan to facilitate participants in accessing various administrative services and information related to the National Health Insurance program, such as participant registration, updating membership data, and obtaining information on healthcare services at primary healthcare facilities and referral hospitals. Although the application was designed to improve access to healthcare services, its utilization among participants remains relatively low. This study aimed to analyze factors associated with the utilization of the Mobile JKN information system among National Health Insurance participants at Grandmed Hospital. This study used a quantitative approach with a cross-sectional design. The study population consisted of 100.040 National Health Insurance participants registered at Grandmed Hospital, and a sample of 100 respondents was determined using the Lemeshow formula. Data were analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using multiple logistic regression. The results show that the majority of respondents (60%) have not utilized the Mobile JKN application. Bivariate analysis shows significant associations between the utilization of Mobile JKN and system quality, information quality, service quality, frequency of use, and net benefits (p < 0.05). Multivariate analysis shows that information quality is the most dominant factor associated with the utilization of Mobile JKN after controlling for system quality and service quality. These findings indicate that improving the quality of information within the applicati on and strengthening outreach to participants are necessary to enhance the utilization of Mobile JKN and improve access to healthcare services.